O Trickster na escola: um estudo sobre a função educativa do mito - Teixeira, Carlos Henrique [UNESP] (2014)
The objective of this research is to identify, from an ethnological survey in a public school in Araraquara, the manifestation of the trickster myth in the narratives of teachers, students , principals and other school community members. Thus, we plan to conduct an inventory of mythemes varied tricksterianos that are repeated recursively on reports revealing the educational function of this myth and its role in framing behavior in everyday school life with regard to the strategies of educators in dealing with the disorder, the manifestation of the students, the experience in the classroom and coping in school environments. We seek to raise in the first place, the various aspects of the trickster mythology by reading the major works in anthropology, psychoanalysis and literature to identify the various facets of this contradictory ancestral figure. Secondly, we seek to ethnological model proposed by Pierre Erny (1982) identified through field research, the tricksterianas manifestations present in school disorder reported by teachers, students and administrators. Finally, the theoretical ground of the imaginary anthropology Gilbert Durand and its developments in the pedagogy of the imagination of Alberto Filipe Araujo and Maria Cecília Sanchez Teixeira, we seek to interpret the data collected with the aim of contributing to the study of the creative function of the trickster and its inevitable connections with school education. We include here the support of everyday socioantropologia Maffesoli that will lead us to the study of ambivalent sensitivities that emerge everyday living in all its drama